MODERN TEACHING METHODS FOR RESTRUCTURING THE CURRICULUM OF BUSINESS EDUCATION IN TECHNICAL SCHOOLS FOR SUSTAINABLE GROWTH, DEVELOPMENT AND GLOBAL ACTIVITY - Najmiddinov, Dilshod (Science technology&Digital finance, 2023)
This study assessed the extent to which modern teaching methods are being applied to restructure the business education curriculum for sustainable development and global relevance as perceived by university business education teachers. The study was guided by one research question and two hypotheses. This study used a survey research design.